Selena the sleepover fairy - Meadows, Daisy (New York : Scholastic, 2012)
Rachel and Kirsty are going to a giant sleepover in the city--and they can't wait! But things are going all wrong. Jack Frost and his goblins have stolen Selena the Sleepover Fairy's three magic objects. Without them, everyone will be losing sleep. Can Rachel and Kirsty help Selena track down her magic, so that sleepovers will be full of fun, games and giggles again?
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Lost articles -- Juvenile fiction; Frost, Jack (Fictitious character) -- Juvenile fiction